2013
DOI: 10.1177/1753425913501098
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestins 1 and 2 are critical regulators of inflammation

Hongkuan Fan

Abstract: β-Arrestins 1 and 2 couple to seven trans-membrane receptors and regulate G protein-dependent signaling, receptor endocytosis and ubiquitylation. Recent studies have uncovered several unanticipated functions of β-arrestins, suggesting that the role of β-arrestins in cell signaling is much broader than originally thought. It is now recognized that β-arrestins can transduce receptor signaling independent of G proteins. The expression of β-arrestins is differentially regulated in immune cells and tissues in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…Since then, several pieces of evidence, when taken together, suggest that β 2 AR-mediated β-arrestin-dependent signaling is pro-inflammatory in asthma. Firstly, β-arrestins have been implicated as regulators of inflammation in a variety of diseases including asthma, sepsis, rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis and atherosclerosis [24,25]. Lung β-arrestin expression is up-regulated in murine models of asthma [10] and is similarly dynamically regulated in other inflammatory diseases [24].…”
Section: β2ar and Par2 Signaling In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several pieces of evidence, when taken together, suggest that β 2 AR-mediated β-arrestin-dependent signaling is pro-inflammatory in asthma. Firstly, β-arrestins have been implicated as regulators of inflammation in a variety of diseases including asthma, sepsis, rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis and atherosclerosis [24,25]. Lung β-arrestin expression is up-regulated in murine models of asthma [10] and is similarly dynamically regulated in other inflammatory diseases [24].…”
Section: β2ar and Par2 Signaling In Asthmamentioning
confidence: 99%
“…Firstly, β-arrestins have been implicated as regulators of inflammation in a variety of diseases including asthma, sepsis, rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis and atherosclerosis [24,25]. Lung β-arrestin expression is up-regulated in murine models of asthma [10] and is similarly dynamically regulated in other inflammatory diseases [24]. Results from multiple murine studies have shown that the asthma phenotype is strikingly diminished in β-arrestin-2 −/− mice irrespective of the method of induction of allergic airway disease [4,12,19].…”
Section: β2ar and Par2 Signaling In Asthmamentioning
confidence: 99%
“…5 However, there is still a limited understanding about the regulatory mechanism of NOD2 on the inflammation of cerebral I/R. 9 Li et al reported ARRB2 acts 6 More recently, β-arrestins have been identified as scaffold proteins binding with various target molecules and thus regulating a wide range of biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Growing evidence shows that β-arrestin 2 (ARRB2) play a critical regulatory role in the inflammatory response. 9 Li et al reported ARRB2 acts…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that ARRB1 and ARRB2 competitively interact with p65 and the interaction is completely dependent on in ammatory stimulation, suggestive of p65 activation-dependent interaction. Previous studies have revealed that the effects of ARRBs on the activation of the NF-κB pathway depend on stimuli and cell types studied [28,59] and the underlying mechanisms may involve direct interaction with IκBα, IKKα, and ΙΚΚβ [49][50][51]. Our data not only suggest a novel mechanism by which ARRBs activate the NF-κB pathway, but also imply distinct functions of ARRBs in PD being attributable to their different abilities to interact with p65.…”
Section: Discussionmentioning
confidence: 54%